The use of mobile phones to compensate for organisational and memory impairment in people with acquired brain injury : a dissertation presented in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Mackie, Cornè (Massey University, 2008)
Objectives: To investigate the extent to which people with memory difficulties use cognitive aids, and to compare this with that of the general population. Relationships between current memory aid use, age, and such factors as insight into functional difficulties, and pre-injury use of memory aids were examined. To investigate the usefulness of mobile phones in compensation for memory impairment following TBI; To investigate the impact of the type of memory impairment (encoding vs. retrieval), level of insight, and familiarity with technology on the use of mobile phones as cognitive aids. Design: Study One - Survey; Study Two - Repeated Single-case ABAB-design Participants: Study One - A group of 29 participants with memory difficulties due to traumatic brain injury (TBI), and an age-matched control group of 33 participants. Study Two - Six participants were selected from people with TBI in New Zealand. Inclusion criteria were a history of TBI, being over 16-years-old, and both self-reported and formally assessed memory difficulties. Measures: Memory Aids Questionnaire; Patient Competency Rating Scale; Shapiro Control Inventory; Task completion forms. Results: Study One - People with TBI and controls tended to use a similar number and type of aids. Electronic memory aids (EMAs) were viewed as more effective in assisting with remembering, but were used less frequently than non-EMAs. This study found that age may impact on the type of aids used. Study Two - All six participants showed statistically significant improvements in the number of tasks remembered while using the phone vs. not using any aids at all. When comparing the phone and the use of traditional aids, five participants showed statistically significant improvements and one performed worse. These results were maintained at one-month follow-up. While the use of mobile phones to assist with remembering is efficacious in some cases, it is not suitable for use with all individuals.
Keywords: Memory disorders; Patients; Rehabilitation; Brain damage; Mnemonics; Cellular telephones